2022
DOI: 10.1038/s41929-022-00796-1
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed Pt and Fe sites and Pt–Fe nanoparticles for durable proton exchange membrane fuel cells

Abstract: Proton exchange membrane fuel cells convert hydrogen and oxygen into electricity without emissions. The high cost and low durability of Pt-based electrocatalysts for the oxygen reduction reaction hinder their wide application, and the development of non-precious metal electrocatalysts is limited by their low performance. Here we design a hybrid electrocatalyst that consists of atomically dispersed Pt and Fe single atoms and Pt–Fe alloy nanoparticles. Its Pt mass activity is 3.7 times higher than that of commer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
162
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 254 publications
(163 citation statements)
references
References 55 publications
1
162
0
Order By: Relevance
“…Carbon-supported Pt nanoparticles (Pt/C) have been popularly applied in the polymer electrolyte fuel cells. The carbon support properties not only affect the fuel cell performance, especially in the high current, but also the long-term stability of the catalyst during harsh fuel cell tests. The low durability of a cathodic Pt/C catalyst during the oxygen reduction reaction (ORR) in fuel cells is because of the severe electrochemical surface area (ECSA) decrease, resulting from metal dissolution, Ostwald ripening, coalescence, and detachment. In addition to the intrinsic unstable factors like small particle sizes, Pt dissolution and detachment are also the consequence of carbon oxidation and corrosion. , Furthermore, the weak cooperation between particles and substrate results in severe coalescence and detachment from the support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Carbon-supported Pt nanoparticles (Pt/C) have been popularly applied in the polymer electrolyte fuel cells. The carbon support properties not only affect the fuel cell performance, especially in the high current, but also the long-term stability of the catalyst during harsh fuel cell tests. The low durability of a cathodic Pt/C catalyst during the oxygen reduction reaction (ORR) in fuel cells is because of the severe electrochemical surface area (ECSA) decrease, resulting from metal dissolution, Ostwald ripening, coalescence, and detachment. In addition to the intrinsic unstable factors like small particle sizes, Pt dissolution and detachment are also the consequence of carbon oxidation and corrosion. , Furthermore, the weak cooperation between particles and substrate results in severe coalescence and detachment from the support.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we also demonstrated that a hybrid catalyst composed of Pt−Fe alloy particles and Pt and Fe atoms did not show activity loss even after 100000 cycles in a fuel cell. 7 It is known that Me−N−C support derived from high-temperature pyrolysis has high intrinsic stability, fine porosity, and graphitization. 30−32 The metal and N doping sites in the support could also mitigate the movement and decrease the coalescence frequency of nanoparticles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…43 It has been suggested that oxygen would be chemically adsorbed on catalysts that are exposed to air and it was not stable in the ORR reaction. 44 The EELS spectra of single-atom Pt do not show perceptible O signals before and after cycling. Thus, we conclude that Pt 3 Co@Pt-SAC is structurally and chemically stable without obvious Pt oxidization.…”
Section: Resultsmentioning
confidence: 96%
“…The weak O K-edge peak should be ascribed to the chemically adsorbed oxygen, which has also been examined by XPS . It has been suggested that oxygen would be chemically adsorbed on catalysts that are exposed to air and it was not stable in the ORR reaction . The EELS spectra of single-atom Pt do not show perceptible O signals before and after cycling.…”
Section: Resultsmentioning
confidence: 99%
“…A similar result is also reported in other literature. 47 To reveal the ORR pathway, both RDE and RRDE measurements have been employed to determine the electron transfer number n of all samples. Fig.…”
Section: Resultsmentioning
confidence: 99%